PERLAWANAN ALAM TERHADAP KOLONIALISME DALAM NOVEL POHON JEJAWI KARYA BUDI DARMA - Maimunah, Maimunah (LITERA, 2014)
This study aims to describe: (1) how colonial ecocriticism is represented, and (2) what text ideologies are like. The short story Pohon Jejawi presents a Dutch colonial setting in Surabaya in the 1930s. The main character was Henry van Kopperlink, a new mayor of Surabaya, who felt disturbed by the existence of a jejawi tree, which was full of mystical myth and mystery. The mystical old tree growing in Kedung Gang Buntu was unable to be chopped down several times because the birds hiding in its dense leaves made every effort to cut it down fail. Using the green studies perspective, this short story presents colonial masculinity represented the main characters; it is unable to be established in Surabaya. The tropical nature represented by the jejawi tree is capable of making the colonial rust en orde chaotic. In Pohon Jejawi, Budi Darma tells that colonialism is opposed not only by the indigenous West Indie people but also by the mysticism of the jejawi tree.